ANALYSIS OF OINTMENT FORMULATION FROM BILIMBI LEAVES (Averrhoa bilimbi) - Santi, Tahara Dilla; Zakaria, Radhiah; Nauval, Muhammad Dharma (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2022)
Averrhoa bilimbi/Bilimbi leaf extract has anti-inflammatory activity in several studies. Development of bilimbi leaf extracts ointment can maximize anti-inflammatory therapy. The purpose of this study was to determine the phytochemical compounds and evaluate bilimbi leaf extract ointment. Method: The leaf compounds examined by phytochemical screening and ointment tests were for their physical properties including pH, organoleptic, and dispersive tests. The organoleptic test and pH test were analyzed descriptively. Spreadability data were analyzed using Kruskal Wallis. Results: Qualitative analysis of bilimbi leaf extract showed a positive reactions of alkaloids to Mayer, Wagner, and Dragendorff, steroids, flavonoids, phenols, terpenoids, and saponins.Meanwhile leaf do not contain tannins. Organoleptic test showed the green ointment with a distinctive aroma of leaves. The pH of the leaves is classified as weakly acidic, close to neutral, which is 5-6. The spreadability of the ointment was not significantly different based on the Kruskal Wallis test. Conclusion: The resulting ointment is predominantly green in color and the ointment formulation has no different in dispersion.